2018
DOI: 10.1186/s12879-018-3101-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and bacteriological features and prognosis of ascitic fluid infection in Chinese patients with cirrhosis

Abstract: BackgroundSpontaneous bacterial peritonitis (SBP) and bacterascites (BA) represent frequent and serious complications in cirrhosis patients with ascites. However, few detailed data are available regarding the clinical and bacteriological feature of SBP or BA patients in China.MethodsWe retrospectively analyzed bacteriological and clinical characteristics of patients with SBP and BA at Beijing 302 Hospital in China from January 2012 to December 2015.ResultsA total of 600 patients with SBP (n = 408) or BA (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
7
23
0
Order By: Relevance
“…The factors related with liver function were consistently significant predictors of PVO patients’ survival (Table 3) (Fig. 2), and these results are in line with the results of other types of infection in patients with cirrhosis 39,40 . The multivariate analysis identified CTP class and MELD score as significant predictors of 30-day and 90-day mortality, respectively (Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…The factors related with liver function were consistently significant predictors of PVO patients’ survival (Table 3) (Fig. 2), and these results are in line with the results of other types of infection in patients with cirrhosis 39,40 . The multivariate analysis identified CTP class and MELD score as significant predictors of 30-day and 90-day mortality, respectively (Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…These mortality rates were comparable to SBP patients from the same centre (34% and 77% respectively). High rates of one‐year mortality were reported from another recent European study (61% in bacterascites and 47% in SBP), while data from China hinted at a lower 30‐day mortality of 192 patients with bacterascites in comparison to 408 patients with SBP (14% vs 26% respectively) . A similar difference in mortality (19% in SBP vs 37% in bacterascites) was described in a French study .…”
supporting
confidence: 59%
“…22,23 Historically, GNB have been isolated in the majority of patients with HBV-related acute decompensated cirrhosis complicated with SAI. 22,24 However, in this study, GPB were found to be the predominant pathogens. Particularly, an increasing rate of infections caused by GPB and resistant microorganisms had been demonstrated in culturepositive cases of SAI.…”
Section: Discussionmentioning
confidence: 99%